Advanced mimo channel estimation techniques: A comprehensive review of methods, algorithms, and performance optimization - Eleje, S.E.; Anioke, C.L.; Ani, C.I. (Nigerian journal of technology, 2025)
The promising characteristic features of Multiple-Input Multiple-Output (MIMO) systems rely on the knowledge of the channel state  information (CSI) for coherent signal data detection. The determination of channel state information is achieved using various  conventional estimation techniques such as pilot-aided, blind, and semi-blind channel estimation techniques. Obtaining accurate channel  state information in MIMO systems is significant tasks upon which system performance depends. This paper presents a  comprehensive review of various MIMO channel estimation techniques presented in literature from conventional techniques to more  recent deep neural network-based techniques. Various ways of pilot arrangement and complexity reduction techniques are discussed.  Furthermore, the key performance indicators in MIMO channel estimation, various algorithms applied in channel estimation and the  impact of outdated CSI with its causes are also presented. The recent improvements on the conventional techniques with its impact on  the key performance indicators in communication systems such as 5G and beyond Networks, Millimeter-wave Communications, and  Massive MIMO system were also reviewed. Accurately estimating wireless channel condition makes signal transmission adaptive leading  to optimal performance in transmission and decoding of signals.